Mechanisms of Post-critical Illness Cardiovascular Disease - Owen, Andrew; Patel, Jaimin M.; Parekh, Dhruv; Bangash, Mansoor N. (Frontiers in Cardiovascular Medicine, 2022)
Prolonged critical care stays commonly follow trauma, severe burn injury, sepsis, ARDS, and complications of major surgery. Although patients leave critical care following homeostatic recovery, significant additional diseases affect these patients during and beyond the convalescent phase. New cardiovascular and renal disease is commonly seen and roughly one third of all deaths in the year following discharge from critical care may come from this cluster of diseases. During prolonged critical care stays, the immunometabolic, inflammatory and neurohumoral response to severe illness in conjunction with resuscitative treatments primes the immune system and parenchymal tissues to develop a long-lived pro-inflammatory and immunosenescent state. This state is perpetuated by persistent Toll-like receptor signaling, free radical mediated isolevuglandin protein adduct formation and presentation by antigen presenting cells, abnormal circulating HDL and LDL isoforms, redox and metabolite mediated epigenetic reprogramming of the innate immune arm (trained immunity), and the development of immunosenescence through T-cell exhaustion/anergy through epigenetic modification of the T-cell genome. Under this state, tissue remodeling in the vascular, cardiac, and renal parenchymal beds occurs through the activation of pro-fibrotic cellular signaling pathways, causing vascular dysfunction and atherosclerosis, adverse cardiac remodeling and dysfunction, and proteinuria and accelerated chronic kidney disease.